Online resources for platelet-rich plasma injections for orthopedic therapy: What are patients reading? A survey of Turkish websites - Çatal, Bilgehan; Çimen, Oğuzhan; Demirtaş, Abdullah; Azboy, İbrahim (Turkish Joint Diseases Foundation, 2020)
Objectives: This study aims to evaluate the quality, accuracy, and readability of Turkish online resources for platelet-rich plasma (PRP) injections for orthopedic therapy.Patients and methods: In this retrospective study. online searches using Google, Yandex. and Yahoo search engines were performed on 21-22-23 May 2019. respectively. "Platelet-rich plasma". "platelet-rich plasma treatment", "PRP", and "PRP treatment" were entered in Turkish into these three search engines. The first 50 websites from each search were collected. The quality and accuracy of online information related to PRP injections for orthopedic therapy were evaluated by three reviewers with the use of scoring criteria specific to PRP. The Flesch-Kincaid (FK) score was used to determine readability.Results: Eighty-six unique websites were evaluated. The average quality and accuracy scores of all websites were 7.1 +/- 4.3 out of a maximum of 25 points and 7.3 +/- 2 out of a maximum of 12 points. respectively. The average FK score of all websites was 10.8 +/- 2.2. Only 27 websites (31.4%) had a FK score that was at or below the eighth-grade level. There were no significant differences among the mean scores of websites categorized by search terms, search results ranking, owners or reading level for both quality and accuracy scores.Conclusion: The information regarding PRP usage in orthopedic conditions provided by Turkish online resources has low quality and low accuracy ratings and is also difficult to read.
Keywords: Accuracy; Health Information; Internet; Online Search; Platelet-Rich Plasma; Quality; Readability